Becoming woman in Vargas Llosa's Fiction: Blazing a trail from La ciudad y los perros to Tiempos recios - AISA PESSAGNO-DELBOY (2023)
This study investigates the evolution of Mario Vargas Llosa’s portrayal of his female characters through detailed analysis of relevant works ranging from La ciudad y los perros (1962) to Tiempos recios (2019). The main purpose is to address an important deficit in the critical study of Vargas Llosa: the analysis of his female characters throughout his work of fiction. This work shows the progression of female identity, the rejection of the patriarchal system and the steady, albeit gradual, growth of women’s power of self-determination. Vargas Llosa’s broader socio-political preoccupations are discussed in each chapter as essential historical background to the works under consideration. An introductory section on the context of each of the periods to be addressed highlights relevant events in the world and in Peru, with particular reference to the writer and to women. This will allow the reader to contextualize the representation of female characters and their roles within society. In his early fiction, women are portrayed as passive, subservient and often victimized by men. Those of indigenous descent are doubly disadvantaged by their low socio-economic status and social exclusion. In subsequent works, women gradually become more prominent (La tía Julia y el escribidor, 1977), more assertive (Travesuras de la niña mala, 2006), more defiant of heterosexual norms (Cinco esquinas, 2016), and more self-determined (Tiempos recios, 2019). Other major aspects of Vargas Llosa relate to his self-professed status as a “realist” writer who diversifies his fiction with autobiography. Driven by his personal demons, his literary themes—which serve as a barometer of his increasingly liberal socio-political perspectives—suggest themselves to the author who feels compelled to investigate them. The author’s unfettered defiance of norms and constraints—in literature as well as in his personal life—allow for an unapologetic and innovative portrayal of women and their various “becomings”, in an ever-evolving world.